2013
DOI: 10.1007/s12264-013-1347-6
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the promoter region of CYP7A1 are associated with neuromyelitis optica but not with multiple sclerosis in the Han Chinese population

Abstract: Multiple sclerosis (MS) and neuromyelitis optica (NMO) are common autoimmune demyelinating disorders of the central nervous system. The exact etiology of each remains unclear. CYP7A1 was reported to be associated with NMO in Korean patients, but this is yet to be confirmed in other populations. In this study, we used Sanger sequencing to detect SNPs in the promoter region of CYP7A1 in a population consisting of unrelated patients and controls from the Han Chinese population (129 MS; 89 NMO; 325 controls). Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Few comprehensive analyses of the association between non-MHC loci and NMO have been reported. A genome-wide association study involving 53 Korean NMO patients and 240 controls found that a promoter SNP in CYP7A1 that encodes cytochrome P450 has a protective role in the risk of NMO [27] , which was replicated in our previous study [16] . Also, the allele of programmed death-1 was found to be associated with NMO [28] .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Few comprehensive analyses of the association between non-MHC loci and NMO have been reported. A genome-wide association study involving 53 Korean NMO patients and 240 controls found that a promoter SNP in CYP7A1 that encodes cytochrome P450 has a protective role in the risk of NMO [27] , which was replicated in our previous study [16] . Also, the allele of programmed death-1 was found to be associated with NMO [28] .…”
Section: Discussionsupporting
confidence: 77%
“…A total of 110 unrelated NMO patients ( [16] . Written informed consent was given by participants >18 years of age and guardians on the behalf of those <18 years old prior to inclusion.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Mb, respectively. CYP7A1 is involved in the synthesis of cholesterol, steroids, and other lipids and is associated with neuromyelitis optica (Zhao et al, 2013). SDCBP encodes protein that binds to a variety of transmembrane proteins.…”
Section: Trait-specific Qtlmentioning
confidence: 99%
“…All subjects were of Han Chinese descent and most participants originated from the association study reported previously (Zhao et al, 2013). MS patients were diagnosed according to the revised McDonald criteria (Polman et al, 2005) and the disability was evaluated by Expanded Disability Status Scale (EDSS).…”
Section: Subjectsmentioning
confidence: 99%